2018
DOI: 10.1007/s10815-018-1380-5
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal versus oral estrogen: clinical outcomes in patients undergoing frozen-thawed single blastocyst transfer cycles without GnRHa suppression, a prospective randomized clinical trial

Abstract: Purpose To conduct a non-inferiority study to compare the clinical outcomes of transdermal estrogen patch and oral estrogen in patients undergoing frozen-thawed single blastocyst transfer non-donor cycles without GnRHagonist (GnRHa) suppression. Methods A total of 317 women with irregular menses or anovulatory cycle undergoing frozen-thawed embryo transfer (FET) non-donor cycles without GnRHa suppression were involved in a prospective randomized clinical trial between M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
0
11
1
2
Order By: Relevance
“…According to our results, provided the follicular diameter and e2 levels are appropriate, hCG can be administered at any time between the start of LH rise (15 IU/L) and LH peak level (> 40 IU/L), without having a detrimental effect on ongoing pregnancy. Furthermore, there was a lower rate of clinical pregnancy losses (6.1%, 5.6%, 6.7%, 7.3%) when compared to our pregnancy losses rate in artificial cycle (17.2%) [21].…”
Section: Discussioncontrasting
confidence: 61%
“…According to our results, provided the follicular diameter and e2 levels are appropriate, hCG can be administered at any time between the start of LH rise (15 IU/L) and LH peak level (> 40 IU/L), without having a detrimental effect on ongoing pregnancy. Furthermore, there was a lower rate of clinical pregnancy losses (6.1%, 5.6%, 6.7%, 7.3%) when compared to our pregnancy losses rate in artificial cycle (17.2%) [21].…”
Section: Discussioncontrasting
confidence: 61%
“…However, it should be noted that the report is a small study with 15 cases of live births in the two groups. In a study comparing patches and oral preparations 5 and a study comparing patches and vaginal tablets, 6 there was no difference in the ongoing pregnancy rate. In recent years, there have been few reports of using subcutaneous injection or intramuscular injection.…”
Section: Discussionmentioning
confidence: 97%
“…First, there are differences in the administration routes such as oral, transdermal, and vaginal. It has been reported that the live birth rate (LBR) did not differ depending on the administration route 4‐6 . Next, there are regimens that mimic changes in serum estradiol during the menstrual cycle to change the dose, and fixed‐dose regimens.…”
Section: Introductionmentioning
confidence: 99%
“…We did not find any other study in the literature comparing these two routes, but found several studies comparing the transdermal to the oral route, with contradictory results. One randomized controlled trial (RCT) found that endometrial thickness was significantly higher with transdermal compared to oral treatment 21 , while two other RCTs failed to find any significant difference in endometrial thickness between the two routes 22,23 .…”
Section: Discussionmentioning
confidence: 99%